2007
DOI: 10.1038/nrm2153
|View full text |Cite
|
Sign up to set email alerts
|

The apoptosome: signalling platform of cell death

Abstract: Recent work on the initial switches that trigger cell death has revealed surprising inventions of nature that ensure the ordered suicide of a cell that has been selected for demise. Particularly intriguing is how a signal--the release of cytochrome c from the mitochondria--is translated into the activation of the death cascade, which leads to a point of no return. Now there is new understanding of how this crucial process is delicately handled by a cytosolic signalling platform known as the apoptosome. The for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
723
0
11

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 922 publications
(750 citation statements)
references
References 53 publications
16
723
0
11
Order By: Relevance
“…Here, we have found that edefosine induces cytochrome c release from mitochondria in pancreatic cancer cells. Cytochrome c released from mitochondria binds to Apaf-1 and pro-caspase-9 to form the so-called apoptosome (Riedl and Salvesen, 2007). This complex catalyzes the activation of caspases that executes the apoptotic cell death program.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we have found that edefosine induces cytochrome c release from mitochondria in pancreatic cancer cells. Cytochrome c released from mitochondria binds to Apaf-1 and pro-caspase-9 to form the so-called apoptosome (Riedl and Salvesen, 2007). This complex catalyzes the activation of caspases that executes the apoptotic cell death program.…”
Section: Discussionmentioning
confidence: 99%
“…As caspase-3 is a well-known executor enzyme in apoptosis pathway Nuclear DNA fragmentation and apoptosome complex formation are critical steps in the apoptotic process [40]. DNA fragmentation tests performed on 2008 cells treated for 24 h with IC 50 concentrations showed the ability of all gold(I) derivatives to increase mono-and oligo-nucleosome formation, although to a different extent (Fig.…”
Section: Apoptosis and Cell Cycle Studiesmentioning
confidence: 97%
“…In the first study [40] Thioredoxin reductase activity was assayed by measuring NADPH-dependent reduction of DTNB at 412 nm (A); glutathione reductase activity (B) and glutathione peroxidase (C) activities were followed at 340 nm. M a n u s c r i p t 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 M a n u s c r i p t a Unless otherwise specified, NMR spectra are recorded in chloroform-d,.…”
Section: Apoptosis and Cell Cycle Studiesmentioning
confidence: 99%
“…It turned out that the apoptosis, interleukin-27, angiopoietin receptor and the PI3K/ MAP kinase pathways are related to these candidate genes. The well-known tumour-suppressor gene, RB1, which was deleted in the RET/PTC-positive group of tumours and which is a key gene in the FAS signalling pathway (Nagata, 1994) is linked to the caspase cascade in the apoptosis pathway by CASP3 (Riedl and Salvesen, 2007). In normal cells an activation of RB1 by CASP3 leads to a repressed transcription of a series of cell cycle proteins by recruiting methyl-transferases that subsequently induce transcription-inactive heterochromatin (Tan and Wang, 1998;Nielsen et al, 2001).…”
Section: Array Cgh On Ptc K Unger Et Almentioning
confidence: 99%